Effects of protein-carbohydrate vs. carbohydrate alone supplementation on immune inflammation markers in endurance athletes: a randomized controlled trial - Moreno-Pérez, D.; López-Samanes, A.; Larrosa, M.; Larumbe-Zabala, E.; Centeno, A.; Roberts, J.; Naclerio, F. (European Journal of Applied Physiology, 2023)
Purpose The impact of ingesting carbohydrates alone or combined with proteins to support exercise immune adaptation in endurance athletes is scarcely investigated. The present study compares the effect of ingesting a combined protein-carbohydrate supplement vs. a carbohydrate-only supplement post-workout on immune inflammation markers following a 10 week periodized endurance training program in well-trained athletes.